Pengaruh Kinerja Keuangan dan BI-7 Day Repo Rate terhadap Profitabilitas pada Bank BUMN - Salsa Bila Azahra; Rosma Pakpahan; Muhamad Umar Mai (Indonesian Journal of Economics and Management, 2021)
The purpose of this research is to describe the effect of Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loan and BI-7 Day Repo Rate on profitability (ROA) at BUMN Bank period 2012-2019. Population and samples in this research are Bank BUMN period 2012-2019 as many as 4 banks (BNI, BRI, BTN and Mandiri Bank). Saturation sampling is the sampling technique used. The BUMN Bank annual report is the secondary data used. Associative and quantitative research methods are the research methods used. The test is done by panel data regression method which is processed using Eviews 9. The selected panel data regression method is the Fixed Effect Model. The results showed that partially CAR had significant effect on profitability. Partially LDR had not significant effect on profitability. Partially NPL had significant effect on profitability. Partially BI7DRR had not significant effect on profitability. Simultaneously, CAR, LDR, NPL and BI7DRR had a significant effect on profitability (ROA) at Bank BUMN.